ENERGY MODELLING AND FORECASTING OF DAERAH ISTIMEWA YOGYAKARTA 2025 - Eko Haryono; Deendarlianto -; Bertha Maya Sopha (Master in Systems Engineering, 2014)
Daerah Istimewa Yogyakarta (DIY) is one of the provinces in Indonesia which does not have a backup or potential sources of non-renewable primary energy. The non-renewable energy demand until this time, such as oil,coal and gas is supplied from the outside. DIY is in Java Madura Bali (JAMALI) interconnerction system and has not had a large-scale power systems. While DIY has renewable energy sources such as hydro, solar, wind, wave and biomass energy. These renewable energy sources are alternative energy that have not been optimally used. The lack of reserve energy resources that resulting dependence of energy supply from other areas should receive special attention from DIY government. To meet energy demand, the energy resources development is required. Due to the energy resources development requires a long time and high cost, it is necessary to be supported by good planning in energy policy.The purpose of this study is to determine the balance of energy demand and supply of DIY until 2025. Furthermore, the purpose of this study is to find out a mix number of renewable energy. The Indonesian government has launched a vision of 25/25 which expection in 2025, the mix number of renewable energy will be 25%.The results of this study indicate that in 2025, the Transportion Sector is the largest energy user sector in DIY at 52.37%, followed by Household Sector (32.70%), Commercial Sector (8.26%), Other Sector (4.64%), and Industrial Sector (2.04%). The high level of energy consumption in the Transportation Sector is caused by the increasing number of vehicles especially motorcycles and passenger cars considering DIY is a student and tourism city. In term of the type of energy used, in 2025, the gasoline is the greatest type of energy demand (41.8%), followed by LPG (23.97%), electricity (18.14%) and diesel oil (11, 74%). This indicates that the fuel oil is still the main energy source for the DIY community activities. When viewed from supply side, most of the energy needs in DIY are supplied from outside. If the development of enewable energy targets DIY reached, the renewable energy mix is obtained by 0.53 %.